Word-final /ɔ̃/ in Greater Poland Polish: A Cumulative Context Effect? - Kaźmierski, Kamil; Szlandrowicz, Marta (Research in Language, 2020)
An empirical corpus-based study of the likelihood of realizing the Polish nasal vowel /ɔ̃/ word-finally as [ɔm] (i.e. of 'nasal stopping') is presented. The goal was to verify whether the phenomenon exhibits a cumulative context effect, with words typically occurring in an environment favoring a particular phonetic variant showing higher rates of that variant regardless of environment. The results show that nasal stopping is more likely before stop-initial words than before words beginning in other sounds, if there is no intervening pause. Results with regard to the hypothesis that words typically followed by stops will show higher likelihood of nasal stopping, however, remain inconclusive.